Crack Formation and Propagation in Molecular Dynamics Simulations of Polymer Liquid Crystals - Brostow, Witold (2002)
In recent papers we have used statistical mechanics to predict multiple phase formation in polymer liquid crystals (PLCs). [1,2] Now we have performed molecular dynamics simulations of PLC copolymers as materials consisting of LC islands in flexible matrices. A method for creating such materials on a computer is described. The overall concentration of the LC units, island size, and spatial distribution of the islands (random, in rows, and evenly distributed throughout the material) were varied. Crack formation and propagation as a function of these parameters were investigated. The local concentration of LC units in each chain has been defined. We found that the probability of a crack initiation site goes symbiotically with the local LC concentration. The first small crack is sometimes a part of the path through which the material breaks, however, although several small cracks may evolve at first, some of these never evolve into larger cracks since crack arrest occurs. The results can be used for creation of real materials with improved mechanical properties. The local volume fraction description of a simulated handdrawn PLC. The LC islands are shown as dark stars circumscribed by circles. Other shades indicate the local concentration - darker regions indicate higher concentration.